(untitled) (Italian Review of Legal History, 2017)
The recent attempts to remove from Italian law the ban of the contingency fee agreement between client and lawyer, culminated, after a few years, with the return to the previously abolished prohibition. This prompted a brief reflection on the reasons and scope of the ban in question, under the particular perspective of legal history, in order to better clarify what are the actual interests involved and what the possible solutions.